ANALISA PERMASALAHAN PADA TOKO PUPUK IMMANUEL - Jeffry Kurniawan; Rena; Rensia Ester Herdinasari; Tina (Bajang Institute, 2021)
Immanuel fertilizer shop is a small-scale business located in a fairly low-lying area that sells various needs for plants or medicines such as urea fertilizer, regent, rat medicine and others. A neat and orderly business process is a big influence for the business that will be run in the future. A business that will be established must have an organizational structure before the planning process, because a business carried out by someone is quite complicated and will cause many problems because it is handled by someone. The purpose of This research is to develop the arrangement of goods in the store so that in the future when a disaster occurs such as a flood, the goods will remain safe. This development method uses business research methods in order to obtain valid data with the aim of discovering or proving knowledge so that it can solve problems. The results showed that the area where the business is located is quite low so it is vulnerable to flooding, therefore the owner must build a multi-storey warehouse to overcome it.